ЧИЗМА ГЕОМЕТРИЯДА МЕТРИК МАСАЛАЛАРНИНГ БЕРИЛИШИНИ ДИЗАЙНЛИ ТАНЛАШГА КРЕАТИВ ЁНДАШУВ - Рихсибоева, Х.; Есбоганова, Б. (SCIENCE and SOCIETY, 2019)
Methods of the optimum choice of the task of the metric tasks is stated in the article, they are: as finding of the shortest distance between point and plane, and between lines of crossbreeding, by way of the rival points on the basis of design requirements so that the decision of the problems was got more demonstrative, reliable and was not beyond the scope of drawing.
Keywords: descriptive geometry; metric problem; rival; point; plane; distance; corner; value; dihedral corner; geometric figure; crossbreeding lines